WORKSHOPS ENVIRONMENTAL SPACE AS CONSTRUCTION OF ENVIRONMENTAL AWARENESS - Azevedo, Leticia Fátima de; Netto, Tatiane Almeida; Silva, Mirele Milani da; Vargas, Letícia Paludo; Hillig, Clayton (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
http://dx.doi.org/10.5902/223611708647 The environmental workshops act as a process of awareness and knowledge of the issue in this work will be analyzedenvironmental workshops developed in the years 2011 and 2012, with the design of Knowledge Architects withstudents from rural school Dr. Honorato de Souza Santos. The methodology used for this study was to developparticipatory research, supported by the institution, inserted in Institutional Project UFSM/Technology Socialinclusion: citizenship, environmental education and agroecology. The objective of the study is to analyze the practiceof environmental workshops as reflection-action process by students for making awareness and environmentalpreservation. The results allowed the students the awareness regarding the preservation and conservation of theenvironment and proximity and interaction between the school and the academic universe. We conclude that theworkshops fulfill the purpose of raising environmental awareness and promoting a process of awareness ofelementary students from school Dr. Honorato de Souza Santos/Cachoeira do Sul-RS.